CuCoNi multi-element transition metal-based difunctional electrocatalyst, preparation method and application

By developing CuCoNi multivariate transition metal-based dual-function electrocatalyst, using the supported alkaline copper salt method and multi-step preparation process to form a heterogeneous junction material, the problem of poor performance of existing electrocatalysts in oxidation and reduction reactions is solved. , achieving efficient, stable and selective electrocatalytic effects.

CN119392299APending Publication Date: 2025-02-07JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575276.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing electrocatalysts perform poorly in electrocatalytic oxidation and electrocatalytic reduction reactions, and it is difficult to catalyze multiple substrates efficiently at the same time, and the stability and selectivity are insufficient.

Method used

Develop a CuCoNi multivariate transition metal-based bifunctional electrocatalyst, prepared by the alkaline-loaded copper salt method, electrodeposition, calcination and hydrothermal method to form N-doped copper, cobalt and nickel-based oxides or hydroxide heterogeneous A junction material, with a nanosphere structure and a mesh-like porous surface.

Benefits of technology

The bifunctionality of the electrocatalyst is realized, which can efficiently catalyze nitrate reduction to ammonia at a lower potential interval, and catalyze the oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid within a wide potential range, showing excellent performance Faraday efficiency and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392299A_ABST
    Figure CN119392299A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of inorganic nano functional materials, and particularly relates to a CuCoNi multi-element transition metal-based difunctional electrocatalyst as well as a preparation method and application thereof. The bifunctional electrocatalyst is loaded on a conductive substrate and is an N-doped copper, cobalt and nickel-based oxide or hydroxide heterogeneous heterojunction material; the ratio of the amount of substance of Cu to the amount of substance of Co in the bifunctional electrocatalyst is 1: (0.1-0.5), and the ratio of the amount of substance of Cu to the amount of substance of Ni is 1: (0.8-1.5); the bifunctional electrocatalyst can be applied to electrocatalytic reduction or electrocatalytic oxidation. The preparation method comprises the following steps: firstly, loading a transition metal basic salt on the conductive substrate by a molten salt method, and constructing a multi-element transition metal oxide / hydroxide heterostructure under the assistance of regulation and control strategies of electro-deposition, calcination and hydrothermal treatment, so as to realize the cathode and anode dual-function characteristic of the electro-catalytic material. The preparation strategy is economical and feasible, environment-friendly, remarkable in cost benefit and easy to realize large-scale industrial application, and has a wide market prospect in the fields of electrocatalytic organic synthesis and new energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of inorganic nano-functional materials, and specifically relates to a CuCoNi multi-element transition metal-based bifunctional electrocatalyst and its preparation method and application Background Art

[0002] In recent years, the energy recycling system with electrocatalysis as the core has received increasing attention from the academic community. Researchers have proposed a strategy to use renewable energy such as wind energy, solar energy, nuclear energy, geothermal energy and hydropower to supply the electrocatalytic reaction system. This strategy aims to use the clean electrons generated during the electrocatalytic reaction as oxidants or reductants to perform electrocatalytic oxidation and electrocatalytic reduction reactions, thereby producing hydrogen, high-value-added fine chemicals, and pharmaceutical intermediates, and achieving the purification of "three wastes" (wastewater, waste gas, and waste residue).

[0003] This series of ideas are all based on electrocatalytic reactions. In electrocatalytic reaction systems, electrocatalysts play a core role. However, most electrocatalysts currently only show good catalytic effects on a certain type of reaction. There are relatively few catalysts that can be used for both electrocatalytic oxidation and electrocatalytic reduction reactions.

[0004] Therefore, there is an urgent need to develop a more efficient, high-yield, highly selective and stable multi-transition metal-based electrocatalyst that can be simultaneously applied to the electrocatalytic oxidation and hydrogenation of various substrates, so as to obtain high-value-added platform compounds in industrial production in an energy-saving and environmentally friendly manner. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a CuCoNi multinary transition metal-based bifunctional electrocatalyst and a preparation method and application thereof.

[0008] The first aspect of the present invention is to provide a CuCoNi multi-transition metal-based bifunctional electrocatalyst, wherein the bifunctional electrocatalyst is supported on a conductive substrate; the bifunctional electrocatalyst is an N-doped copper, cobalt and nickel-based oxide or hydroxide multiphase heterojunction material;

[0009] Furthermore, the molar ratio of Cu and Co in the bifunctional electrocatalyst is 1:0.1-0.5, and the molar ratio of Cu and Ni is 1:0.8-1.5;

[0010] Furthermore, the bifunctional electrocatalyst can be applied to electrocatalytic reduction or electrocatalytic oxidation.

[0011] Furthermore, the bifunctional electrocatalyst presents a uniform nano-spherical structure, and the surface is densely covered with fine mesh-like porous structures.

[0012] The second aspect of the present invention is to provide a method for preparing a CuCoNi multi-element transition metal-based bifunctional electrocatalyst, comprising the steps of:

[0013] S1. Immersing the conductive substrate in a copper source solution to obtain a substrate loaded with basic copper salt after the reaction, washing and drying for later use;

[0014] S2. constructing a three-electrode electrodeposition system with the basic copper salt-loaded substrate prepared in step S1 as the working electrode, wherein the electrolyte is a cobalt source solution, electrodepositing cobalt, washing and drying, and then calcining and annealing in an inert atmosphere;

[0015] S3. The material obtained in step S2 is subjected to a hydrothermal reaction with a nickel source solution in an alkaline environment, and the CuCoNi multi-transition metal-based bifunctional electrocatalyst can be obtained after washing and drying.

[0016] Furthermore, in step S1, the substrate material includes but is not limited to one or more of foamed nickel, foamed copper, and stainless steel mesh;

[0017] In some embodiments of the present invention, the substrate material is nickel foam.

[0018] Further, in step S1, the copper source solution is any one of an aqueous solution of a copper salt, an ionic liquid solution of a copper salt, and a low-temperature molten salt of a copper salt;

[0019] Furthermore, the low-temperature molten salt is at least one of copper salts having a melting point below 400°C;

[0020] Furthermore, the ionic liquid solution of the copper salt is a molten salt that is in a liquid state at a temperature below 100° C., including but not limited to one or more of copper imidazoles, ammonium salts, and tetrafluoroborate;

[0021] In some embodiments, the copper source is at least one of copper nitrate, chloride, sulfate, phosphate, acetate, and carbonate.

[0022] Furthermore, in step S1, the reaction temperature is 130-150° C., and the reaction time is 15-60 min.

[0023] Furthermore, in step S2, during the electrodeposition process, the working electrode is a conductive substrate loaded with basic copper salt, the counter electrode is a graphite rod electrode, a platinum sheet or a platinum mesh electrode, the reference electrode is a calomel electrode, the electrodeposition potential is -1V vs. SCE, and the electrodeposition time is 500 to 1500s;

[0024] Furthermore, in step S2, the calcination annealing process is carried out in a muffle furnace, the heating rate is 3-5°C / min, and the calcination time is 1-5h. In some embodiments of the present invention, the annealing time is 3h.

[0025] In some embodiments of the present invention, the cobalt source includes but is not limited to at least one of nitrate, chloride, sulfate, phosphate, acetate, and carbonate of cobalt;

[0026] In some embodiments of the present invention, in step S1 and step S2, the washing step uses water or anhydrous ethanol for washing and is dried in a vacuum drying oven; the drying temperature is 60° C. and the time is 6 hours.

[0027] Further, in step S3, the hydrothermal reaction pH is 9-10, the hydrothermal temperature is 100-110° C., and the hydrothermal time is 8-12 h;

[0028] In some embodiments of the present invention, the nickel source includes but is not limited to at least one of nickel nitrate, chloride, sulfate, phosphate, acetate and carbonate.

[0029] In some preferred embodiments, in step S1, the size of the nickel foam substrate is 4 cm×4 cm. When immersed in the copper source solution, the temperature is maintained at 130-150° C. for 15-60 min. The ultrasonic time is 10 min, and the vacuum drying temperature is 60° C. for 6 h.

[0030] In some preferred embodiments, in step S2, the substrate loaded with basic copper salt is subjected to an electrodeposition process in a single electrolytic cell, the working electrode is a 1 cm×1 cm conductive substrate loaded with basic copper salt, the counter electrode is a graphite rod electrode, a platinum sheet or a platinum mesh electrode, the reference electrode is a calomel electrode, the electrodeposition potential is -1 V vs. SCE, and the electrodeposition time is 500 to 1500 s. The conductive substrate after electrodeposition of cobalt is subjected to a calcination annealing process in a tube furnace or a muffle furnace, wherein the heating rate is 3 to 5°C / min, the calcination time is 3 hours, and the calcination atmosphere is high-purity argon.

[0031] In some preferred embodiments, in step S3, the calcined conductive substrate is transferred into an alkaline environment nickel source aqueous solution and stirred for 1 hour. The alkaline environment aqueous solution is prepared by urea, sodium carbonate, potassium carbonate, sodium hydroxide or potassium hydroxide, with a specific pH of 9-10, a hydrothermal temperature of 100-110°C, and a hydrothermal time of 8-12 hours.

[0032] The third aspect of the present invention is to provide the application of CuCoNi multi-transition metal-based bifunctional electrocatalyst in electrochemical catalysis, which is applied to electrocatalytic reduction and / or electrocatalytic oxidation; when applied to electrocatalytic reduction, the bifunctional electrocatalyst is used as a cathode electrocatalyst; when applied to electrocatalytic oxidation, the bifunctional electrocatalyst is used as an anode electrocatalyst.

[0033] Furthermore, the bifunctional electrocatalyst is used as a cathode electrocatalyst for the reduction of nitrates and nitrites to produce ammonia, the reduction of organic nitrobenzenes and their derivatives to amines, and the electrocatalytic decomposition of water to produce hydrogen;

[0034] Furthermore, the bifunctional electrocatalyst is used as an anode electrocatalyst for electrocatalytic oxidation of organic alcohols, organic aldehydes and biomass to produce high value-added chemicals.

[0035] In some embodiments, the application system of the CuCoNi multinary transition metal-based bifunctional electrocatalyst in electrochemical catalysis is a three-electrode system, using an H-type electrolytic cell, the three-electrode system includes a working electrode, a counter electrode, and a reference electrode; the bifunctional electrocatalyst is arranged at the working electrode; the pH of the electrolyte solution is in the range of 12 to 14,

[0036] In some preferred embodiments, when applied to electrocatalytic reduction, the reduction electrolysis voltage is -0.5 to 0 V vs. RHE.

[0037] In some preferred embodiments, when applied to electrocatalytic oxidation, the oxidation electrolysis voltage is 1-2 V vs. RHE.

[0038] In some embodiments of the present invention, the CuCoNi multi-transition metal-based bifunctional electrocatalyst is applied to nitrate-containing wastewater treatment, soil treatment, and waste gas treatment;

[0039] In some embodiments of the present invention, it is applied to the field of synthesis of pharmaceutical intermediates;

[0040] In some embodiments of the present invention, it is applied to the field of synthesis of fine organic chemical intermediates;

[0041] In some embodiments of the present invention, the present invention is applied in the field of new energy, such as water electrolysis to produce hydrogen, fuel cells, and zinc-air batteries.

[0042] As a preferred embodiment of the preparation method of the present invention, the application system is a three-electrode system, an H-type electrolytic cell is adopted, a stone mill rod / platinum sheet is used as a counter electrode, a reference electrode is HgO / Hg, the electrolyte solution is a KOH or NaOH aqueous solution, the pH is in the range of 12 to 14, and when applied to electrocatalytic reduction, the reduction electrolysis voltage is -0.5 to 0 V vs. RHE, and when applied to electrocatalytic oxidation, the oxidation electrolysis voltage is 1 to 2 V vs. RHE, and the constant voltage reaction is for more than 1 hour.

[0043] In some embodiments of the present invention, there is provided an application of the CuCoNi multi-transition metal-based bifunctional electrocatalyst in electrocatalytic reduction of nitrate to produce ammonia, or oxidation of 5-hydroxymethylfurfural to electrosynthesize 2,5-furandicarboxylic acid.

[0044] Beneficial effects of the present invention:

[0045] (1) The present invention provides a CuCoNi multi-transition metal-based oxide hydroxide surface mesh nano-spherical heterojunction material; realizes the dual functional characteristics of the cathode and anode of the electrocatalytic material; the bifunctional electrocatalyst has a unique advantage of multiple active sites and can be applied to electrocatalytic reduction and electrocatalytic oxidation.

[0046] (2) The CuCoNi multi-element transition metal-based electrocatalyst prepared by the present invention has excellent bifunctional catalytic properties. While the anode promotes the production of high-value chemicals, the cathode produces ammonia or aromatic amine compounds, showing significant energy-saving and environmental protection advantages. It is environmentally friendly and cost-effective, easy to achieve large-scale industrial application, and has broad market prospects in the field of industrial electrocatalytic organic synthesis technology and new energy.

[0047] (3) The present invention also provides a method for preparing the material. First, the transition metal basic salt is efficiently loaded on the conductive substrate through the molten salt method, and then a fine control strategy of electrodeposition, subsequent calcination and hydrothermal treatment is used to accurately construct a multi-transition metal oxide / hydroxide heterostructure. The process is simple, the yield is high, the environmental pollution is small, the raw material price is low, the production cost is low, and it can be mass-produced, meeting the requirements of industrial applications.

[0048] (4) When applied to electrocatalytic reduction, this material can efficiently convert nitrate into ammonia in a relatively low potential range, showing excellent Faradaic efficiency (≥94.5%) and an ammonia generation rate of up to 44.1 mg h -1 cm -2 , and has a cycle stability of more than 15 times. When applied to electrocatalytic oxidation, it can efficiently oxidize 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid in a wide potential range, with a yield, Faraday efficiency and raw material conversion rate exceeding 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0050] The electrode material is a CuCoNi multinary transition metal-based oxide hydroxide heterojunction material, which is referred to as CuCoNi for short;

[0051] Figure 1 The powder X-ray diffraction patterns of the typical CuCoNi electrode material described in Example 1, the CuCo electrode material described in Comparative Example 2, and the CuNi electrode material described in Comparative Example 3;

[0052] Figure 2 This is the EDX elemental analysis spectrum of the typical CuCoNi electrode material described in Example 1;

[0053] Figure 3 The XPS full spectrum of the typical CuCoNi electrode material described in Example 1 and the detailed spectra of C1s, N 1s, O 1s, Cu2p, Cu LMM, Co 2p and Ni 2p;

[0054] Figure 4 Physical pictures of the typical CuCoNi electrode material described in Example 1, the CuO electrode material described in Comparative Example 1, the CuCo electrode material described in Comparative Example 2, and the CuNi electrode material described in Comparative Example 3;

[0055] Figure 5 The SEM images of the typical CuCoNi electrode material described in Example 1 at different magnifications are shown;

[0056] Figure 6 5 mVs for the typical CuCoNi electrode material described in Example 1, the CuO electrode material described in Comparative Example 1, the CuCo electrode material described in Comparative Example 2, and the CuNi electrode material described in Comparative Example 3 -1 Polarization curves at scanning rates;

[0057] Figure 7 The typical CuCoNi electrode material prepared in Examples 1 to 11 is used for cathode electrocatalytic reduction of 50 mM NO3 under alkaline conditions. - , 5mVs -1 Polarization curves at scanning rates;

[0058] Figure 8The typical CuCoNi electrode material described in Example 1, the CuO electrode material described in Comparative Example 1, the CuCo electrode material described in Comparative Example 2, and the CuNi electrode material described in Comparative Example 3 were prepared in a solution containing 50 mM NO3 - Comparison of ammonia production performance at different working potentials in 1M NaOH electrolyte;

[0059] Fig. 9 The typical CuCoNi electrode material described in Example 1, the CuO electrode material described in Comparative Example 1, the CuCo electrode material described in Comparative Example 2, and the CuNi electrode material described in Comparative Example 3 were prepared in a solution containing 50 mM NO3 - In 1M NaOH electrolyte, the production of NH3 and NO2 at different working potentials - Corresponding Faraday efficiency comparison chart;

[0060] Fig.10 The typical CuCoNi electrode material described in Example 1 was prepared in a solution containing 50 mM NO3 - 15 cycles of reaction performance at -0.4V vs.RHE in 1M NaOH electrolyte;

[0061] Fig.11 The typical CuCoNi electrode material described in Example 1 is used for the anode electrocatalytic oxidation of 20mMHMF under alkaline conditions, 5mVs -1 Polarization curves at scanning rates;

[0062] Fig.12 This is a comparison chart of HMF conversion, FDCA yield and Faraday efficiency at different working potentials for the typical CuCoNi electrode material described in Example 1 in a 1M NaOH electrolyte containing 20 mM HMF. DETAILED DESCRIPTION

[0063] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0064] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0065] The preparation of the electrode material in the embodiment is obtained by loading basic copper salt method, calcination after electrodeposition and hydrothermal method. The foamed nickel is immersed in a copper nitrate aqueous solution and kept at 130-150°C for 15-60 minutes to obtain in-situ grown basic copper nitrate (denoted as CuNH / NF); the conductive substrate loaded with basic copper salt constitutes a typical three-electrode electrodeposition system in a single electrolytic cell, the electrolyte is a pure cobalt source aqueous solution, the electrodeposition potential is -1V vs.SCE, and the electrodeposition time is 500-1500s. The conductive substrate after electrodeposition of cobalt is subjected to calcination annealing process in a tube furnace or a muffle furnace, the heating rate is 3-5°C / min, the calcination time is 3h, and the calcination atmosphere is high-purity argon. The calcined substrate is transferred to an alkaline environment nickel source aqueous solution (pH 9-10), stirred for 1h, and hydrothermally heated at a temperature of 100-110°C for 8-12h. The prepared sample was washed with anhydrous ethanol and deionized water for more than three times, and vacuum dried at 60° C. for 10 h to obtain the prepared electrode material.

[0066] Example 1

[0067] The present invention provides a large-scale preparation method of a CuCoNi multi-element transition metal-based heterojunction material:

[0068] (1) 10 g of copper nitrate trihydrate was placed in a 100 mL polytetrafluoroethylene inner tube and kept at 140°C for 6 h until it melted. A 4 cm*4 cm nickel foam substrate was placed flat in the inner tube and immersed in the molten copper nitrate to obtain basic copper nitrate (CuNH) grown in situ on the nickel foam.

[0069] (2) CuNH was ultrasonically treated in water and anhydrous ethanol for 10 min respectively, and finally, CuNH was placed in a vacuum drying oven at 60°C for 6 h; the foam nickel substrate loaded with basic copper salt was subjected to electrodeposition in a single electrolytic cell, the working electrode was a 1 cm×1 cm conductive substrate loaded with basic copper salt, the counter electrode was a graphite rod electrode, the reference electrode was a calomel electrode, the electrolyte solution was 50 mL of 0.1 M cobalt nitrate hexahydrate, the electrodeposition potential was -1 V vs. SCE, the electrodeposition time was 600 s, and after deposition, it was washed with anhydrous ethanol and deionized water for more than 3 times, and placed in a vacuum drying oven at 60°C for 6 h. Then, it was transferred to a tube furnace for high-temperature thermal annealing at 350°C for 3 h, the heating rate was 3°C / min, and the calcination inert atmosphere was high-purity argon.

[0070] (3) Weigh 0.291 g (1 mmol) of nickel nitrate hexahydrate and 0.6 g (10 mmol) of urea, dissolve them in 50 mL of deionized water, slowly stir for 1 h, and transfer them into a 50 mL hydrothermal kettle. Put the calcined electrode material into the kettle and perform hydrothermal reaction at 100 °C for 12 h. After naturally cooling to room temperature, wash with anhydrous ethanol and deionized water for more than 3 times, and vacuum dry at 60 °C for 6 h to obtain the prepared electrode material CuCoNi.

[0071] Example 2

[0072] The difference from Example 1 is that in step (1), the copper source is copper sulfate pentahydrate, the substrate is nickel foam, the melting temperature is 140° C., the time is 30 min, the cobalt source in step (2) is cobalt sulfate, and the nickel source in step (3) is nickel sulfate. The other experimental settings are the same as in Example 1.

[0073] Example 3

[0074] The difference from Example 1 is that in step (1), the copper source is cupric chloride dihydrate, the substrate is nickel foam, the melting temperature is 140° C., the time is 20 min, the cobalt source in step (2) is cobalt chloride, and the nickel source in step (3) is nickel chloride. The other experimental settings are the same as in Example 1.

[0075] Example 4

[0076] The difference from Example 1 is that in step (1), the substrate is foam copper, the melting temperature is 150° C., and the time is 60 min. Other experimental settings are the same as in Example 1.

[0077] Example 5

[0078] The difference from Example 1 is that the electrodeposition time in step (2) is 1200 s, and the other experimental settings are the same as Example 1.

[0079] Example 6

[0080] The difference from Example 1 is that in step (2), the concentration of the electrodeposited electrolyte cobalt nitrate is 0.2 M, the electrodeposition time is 1200 s, and the other experimental settings are the same as Example 1.

[0081] Example 7

[0082] The difference from Example 1 is that in step (3), the hydrothermal temperature is 110° C. and the hydrothermal time is 12 h. The other experimental settings are the same as those in Example 1.

[0083] Example 8

[0084] The difference from Example 1 is that the hydrothermal system in step (3) is 0.2 mmol of hexahydrate nitric acid, 5 mmol of urea, and 50 mL of deionized water. The other experimental settings are the same as those in Example 1.

[0085] Example 9

[0086] The difference from Example 1 is that the hydrothermal system in step (3) is 0.1 mmol of hexahydrate nitric acid, 10 mmol of urea, and 50 mL of deionized water. The other experimental settings are the same as those in Example 1.

[0087] Example 10

[0088] The difference from Example 1 is that in step (3), the hydrothermal system is 0.1 mmol of hexahydrate nitric acid, 50 mL of deionized water, and 0.01 M sodium hydroxide solution is added to adjust the solution pH to 10. The other experimental settings are the same as those in Example 1.

[0089] Embodiment 11

[0090] The difference from Example 1 is that in step (3), the hydrothermal system is 0.1 mmol of hexahydrate nitric acid, 50 mL of deionized water, and 0.1 M potassium carbonate solution is added to adjust the solution pH to 10. The other experimental settings are the same as those in Example 1.

[0091] Comparative Example 1

[0092] (1) 10 g of copper nitrate trihydrate was placed in a 100 mL polytetrafluoroethylene inner tube and kept at 140°C for 6 h until it melted. A 4 cm*4 cm nickel foam substrate was placed flat in the inner tube and immersed in the molten copper nitrate for 15 min to obtain basic copper nitrate grown in situ on the nickel foam.

[0093] (2) CuNH was ultrasonically treated in water and anhydrous ethanol for 10 min respectively, and finally, CuNH was placed in a vacuum drying oven at 60°C for 6 h; then, it was transferred to a tube furnace for high-temperature thermal annealing at 350°C for 3 h, with a heating rate of 3°C / min, and the calcination inert atmosphere was high-purity argon, to obtain the prepared electrode material, which was recorded as CuO.

[0094] Comparative Example 2

[0095] (1) 10 g of copper nitrate trihydrate was placed in a 100 mL polytetrafluoroethylene inner tube and kept at 140°C for 6 h until it melted. A 4 cm*4 cm nickel foam substrate was placed flat in the inner tube and immersed in the molten copper nitrate for 15 min to obtain basic copper nitrate grown in situ on the nickel foam.

[0096] (2) CuNH was ultrasonically treated in water and anhydrous ethanol for 10 min respectively, and finally, CuNH was placed in a vacuum drying oven at 60°C for 6 h; the foam nickel substrate loaded with basic copper salt was subjected to electrodeposition in a single electrolytic cell, the working electrode was a 1 cm×1 cm conductive substrate loaded with basic copper salt, the counter electrode was a graphite rod electrode, the reference electrode was a calomel electrode, the electrolyte solution was 50 mL of 0.1 M cobalt nitrate hexahydrate, the electrodeposition potential was -1 V vs. SCE, the electrodeposition time was 600 s, and after deposition, it was washed with anhydrous ethanol and deionized water for more than 3 times, and placed in a vacuum drying oven at 60°C for 6 h. Then, it was transferred to a tube furnace for high-temperature thermal annealing at 350°C for 3 h, the heating rate was 3°C / min, and the calcination inert atmosphere was high-purity argon gas to obtain the prepared electrode material, recorded as CuCo.

[0097] Comparative Example 3

[0098] (1) 10 g of copper nitrate trihydrate was placed in a 100 mL polytetrafluoroethylene inner tube and kept at 140°C for 6 h until it melted. A 4 cm*4 cm nickel foam substrate was placed flat in the inner tube and immersed in the molten copper nitrate for 15 min to obtain basic copper nitrate grown in situ on the nickel foam.

[0099] (2) CuNH was ultrasonically treated in water and anhydrous ethanol for 10 min respectively, and finally, CuNH was placed in a vacuum drying oven at 60 °C for 6 h, and then transferred to a tube furnace for high-temperature thermal annealing at 350 °C for 3 h, with a heating rate of 3 °C / min, and the calcination inert atmosphere was high-purity argon.

[0100] (3) Weigh 0.291 g (1 mmol) of nickel nitrate hexahydrate and 0.6 g (10 mmol) of urea, dissolve them in 50 mL of deionized water, slowly stir for 1 h, and transfer them into a 50 mL hydrothermal kettle. Put the calcined electrode material into the kettle and perform a hydrothermal reaction at 100° C. for 12 h. After naturally cooling to room temperature, wash the mixture with anhydrous ethanol and deionized water for more than 3 times, and vacuum dry the mixture at 60° C. for 6 h to obtain the prepared electrode material, which is recorded as CuNi.

[0101] Crystal structure analysis of CuCoNi multi-transition metal-based electrocatalysts:

[0102] Powder X-ray diffraction was carried out on a D8 X-ray powder diffractometer from Bruker, Germany, with a fixed target monochromatic light source of Cu-Kα and a wavelength of The scanning range was 5-80°, and the scanning step was 0.02°. Sample 1# was a typical electrode material prepared in Example 1, such as Figure 1 The X-ray diffraction pattern obtained by fitting is consistent with Figure 1By comparing the spectra obtained by X-ray diffraction test after scraping the powder from sample 1#, it can be found that the prepared heterojunction contains CuO (PDF#97-006-9094), Co3O4 (PDF#97-000-9362) and 3Ni(OH)2·2H2O (PDF#97-002-4015), indicating that under this simple, mild and environmentally friendly condition, basic copper nitrate can be easily grown on nickel foam in the form of molten salt on a large scale, and then a cobalt source is introduced by electrodeposition, calcination changes the cobalt loading species, and a nickel source is introduced by hydrothermal method to smoothly form a regular CuCoNi ternary transition metal-based oxide hydroxide multiphase heterojunction electrode material on the substrate. In addition, from Figure 2 From the EDX spectrum, it can be found that the main components of the material are Cu, Co, Ni, O, and N, which further proves that the obtained material is a CuCoNi-based oxide hydroxide multiphase heterojunction material.

[0103] Characterization test of CuCoNi multi-transition metal-based electrocatalysts:

[0104] Figure 4 The following are the physical pictures of the typical CuCoNi electrode material described in Example 1, the CuO electrode material described in Comparative Example 1, the CuCo electrode material described in Comparative Example 2, and the CuNi electrode material described in Comparative Example 3. In order to further explore the structural characteristics of the CuCoNi electrocatalyst in Example 1, SEM was used to characterize and analyze its morphology ( Figure 5 ), the CuCoNi electrocatalyst prepared in Example 1 presents a highly regular and relatively uniform nano-spherical structure, and its surface is densely covered with fine mesh-like porous structures. Compared with similar materials described in existing literature, the CuCoNi electrocatalyst of the present invention has a more significant and intuitive pore distribution and a richer specific surface area, which increases the contact surface between the catalyst and the reaction substrate, exposes more reactive sites, and thus can greatly improve the catalytic activity of the electrocatalyst.

[0105] Figure 3 This is an x-ray photoelectron spectroscopy (XPS) diagram of the CuCoNi electrode material described in Example 1. The full XPS spectrum confirms the presence of N, O, Cu, Co and Ni on the surface of the electrocatalyst, which is consistent with the results of EDS. Figure 3 The Cu 2p high-resolution spectrum shown in e shows four main peaks at 954.9 eV, 952.9 eV, 934.9 eV and 933.4 eV, which belong to Cu 2+ 2p 1 / 2, Cu 1+ / Cu 0 2p 1 / 2 ,Cu 2+ 2p 3 / 2 and Cu1+ / Cu 0 2p 3 / 2 , Cu LMM was fitted by the least square method to obtain Figure f, Cu 2+ The highest content, with a small amount of Cu 1+ and Cu 0 This may be due to the fact that a small amount of CuO was reduced to a lower valence state during the electrodeposition process. Figure 3 The strongest peaks in the Co 2p high-resolution spectrum shown in g can be deconvoluted into three peaks at 783.1 eV, 779.8 eV, and 775.5 eV, corresponding to Co 2+ 2p 3 / 2 ,Co 3+ 2p 3 / 2 and Co 0 2P 3 / 2 , combined with the XRD results, it is inferred that there is Co3O4 component in the electrocatalyst. Figure 3 The Ni 2p high-resolution spectrum shown in h shows well-resolved peaks at 873.9 eV and 856.0 eV, which are consistent with the Ni 2+ Ni2p 1 / 2 and Ni 2p 3 / 2 Corresponding. Figure 3 The O1s high-resolution spectrum shown in d is deconvoluted into four peaks. The peak at 532.2 eV is a strong peak caused by common oxygen vacancies, indicating that there are abundant oxygen vacancies in the synthesized material. The peaks at 533.4 eV, 532.1 eV and 529.7 eV correspond to H2O molecules, OH and metal oxygen bonds adsorbed on the surface of the material. Figure 3 c is the high-resolution spectrum of N1s, where the peak at 406.8 eV is attributed to the NO single bond of nitrate. Nitrate may come from the decomposition of basic copper nitrate during the subsequent material synthesis steps. The peaks at 399.2 eV and 398.1 eV correspond to Cu-N bonds and Ni-N bonds, which are caused by the successful doping of N on CuO and Ni(OH)2. The formation of Cu-N bonds is due to the large amount of NH3 produced during the molten salt synthesis process. The formation of Ni-N bonds may be due to the NO3 dissolved by basic copper nitrate. - All these results demonstrate the successful synthesis of N-doped CuO@Co3O4@Ni(OH)2 / NF catalysts with abundant oxygen vacancies.

[0106] Polarization curves of CuCoNi multi-transition metal-based electrocatalysts for electrocatalytic reduction of nitrate

[0107] The CuCoNi electrode material was used as the working electrode, and the Hg / HgO electrode and Pt sheet were used as the reference electrode and counter electrode respectively. The diaphragm was a Nafion proton exchange membrane, and a 1M sodium hydroxide solution containing or not containing 50mM sodium nitrate (NaNO3) was used as the electrolyte. The electrochemical workstation was Shanghai Chenhua 760E, with a charge of 5mV·s -1 The polarization curve test of linear sweep voltammetry (LSV) was carried out at a rate of 5.5. Before the LSV test, argon gas was introduced into the electrolyte until it was saturated, and the electrode material was scanned at 100 mV / s for 20 cycles to allow the electrode material to reach a stable state, and then the test was carried out at a scan rate of 5 mV / s. The potential value was calculated according to the equation E vs.RHE=E vs.Hg / HgO+0.098+0.059·pH, where E vs.RHE is the relative reversible hydrogen electrode potential (V), and E vs.Hg / HgO is the relative Hg / HgO electrode potential (V).

[0108] The polarization curve is Figure 6 As shown in the figure, it can be seen that the CuCoNi electrode material described in Example 1 has excellent performance when used for nitrate reduction under alkaline conditions, and its reaction current density is greatly improved compared with the CuO described in Comparative Example 1, the CuCo described in Comparative Example 2, and the CuNi described in Comparative Example 3. The current density of the CuCoNi electrode material prepared in Example 1 can exceed 200 mA / cm at about -0.05 V (vs RHE). 2 , meeting industrial current density requirements and can be used in industrial production applications.

[0109] Figure 7 The typical CuCoNi electrode material prepared in Examples 1 to 11 is used for cathode electrocatalytic reduction of 50 mM NO3 under alkaline conditions. - , 5mVs -1 Polarization curves at scanning rates show that the current density of the CuCoNi electrode material prepared in Example 1 is the largest, and changing the immersion time of the conductive substrate in the molten salt and the cobalt source electrodeposition time has little effect on the LSV curve current.

[0110] Example 12 Reaction performance of CuCoNi electrocatalyst in electrocatalytic reduction of nitrate to produce ammonia

[0111] The CuCoNi electrode material was used as the working electrode, and the Hg / HgO electrode and Pt sheet were used as the reference electrode and counter electrode, respectively. The diaphragm was a Nafion proton exchange membrane. A 1M sodium hydroxide solution containing 50mM sodium nitrate (NaNO3) was used as the electrolyte. Constant potential electrolysis was carried out for 1h at different working potentials, and the product was quantitatively determined using an ultraviolet spectrophotometer.

[0112] Figure 8It is a comparison chart of the ammonia production of CuCoNi prepared in Example 1, CuO prepared in Comparative Example 1, CuCo prepared in Comparative Example 2, and CuNi prepared in Comparative Example 3. In the potential range of -0.5 to -0.1 V vs. RHE, the ammonia production of each electrode material gradually increases with the increase of potential. At each potential, the ammonia production of CuCoNi described in Example 1 is significantly greater than that of CuO described in Comparative Example 1, CuCo described in Comparative Example 2, and CuNi described in Comparative Example 3.

[0113] like Fig. 9 As shown, at each potential, the Faraday efficiency of ammonia production of CuCoNi in Example 1 is significantly greater than that of CuO described in Comparative Example 1, CuCo described in Comparative Example 2, and CuNi described in Comparative Example 3, and the Faraday efficiency of nitrite production of CuCoNi described in Example 1 is significantly lower than that of CuO prepared in Comparative Example 1, CuCo prepared in Comparative Example 2, and CuNi prepared in Comparative Example 3. This means that the CuCoNi described in Example 1 has a higher charge utilization rate, producing a large amount of ammonia while accumulating the least amount of nitrite. The Faraday efficiency of ammonia production of CuCoNi prepared in Example 1 reached the highest at a potential of -0.4V vs. RHE, which was 94.5%, and the ammonia production per hour was about 44.1mg h -1 cm -2 , which is at a high level in the existing electrocatalytic nitrate reduction research.

[0114] like Fig.10 As shown, at a potential of -0.4V vs. RHE, the cyclic stability of the CuCoNi electrode material prepared in Example 1 was tested. The CuCoNi electrode material prepared in Example 1 was used for electrocatalytic nitrate production of ammonia. After 15 cycles of use, the current retention rate was greater than 85%, and the ammonia production did not decrease significantly. The Faraday efficiency was greater than 90%. This shows that the prepared CuCoNi electrocatalyst has excellent catalytic stability and cyclic practicality, which is conducive to its application and promotion in industry. Polarization curve of CuCoNi electrocatalyst used in electrocatalytic oxidation of HMF to produce FDCA

[0115] The CuCoNi electrode material prepared in Example 1 was placed in an H-type electrolytic cell as a working electrode, a Hg / HgO electrode and a Pt sheet were used as a reference electrode and a counter electrode, respectively, a Nafion proton exchange membrane was used as a diaphragm, and a 1M sodium hydroxide solution containing or not containing 20mMHMF was used as an electrolyte. The polarization curve of linear sweep voltammetry (LSV) was tested at a rate of 5mV / s on a Shanghai Chenhua 760E electrochemical workstation. Before the LSV test, argon was introduced into the electrolyte to saturation, and 20 cycles were scanned at 100mV / s to allow the electrode material to reach a stable state, and then the test was performed at a scan rate of 5mV / s.

[0116] Depend on Fig.11 As shown in the figure, compared with the LSV curve without adding 20 mM HMF, the LSV curve with adding 20 mM HMF has a significant current increase, 100 mA cm -2 At the current density, the overpotential is 253 mV. The starting potential of the LSV curve without adding 20 mM HMF is 1.333 V, and the starting potential of the LSV curve after adding 20 mM HMF is 1.221 V, and the starting potential advance is 112 mV, which shows that the CuCoNi electrode material prepared in Example 1 has strong reaction kinetics for the electrocatalytic oxidation of HMF, and also shows that the CuCoNi electrode material prepared in Example 1 has dual functional effects of electrocatalytic oxidation and electrocatalytic reduction.

[0117] Example 13: Reaction performance of CuCoNi electrocatalyst for electrocatalytic oxidation of HMF to produce FDCA

[0118] The CuCoNi electrode material prepared in Example 1 was placed in an H-type electrolytic cell and used as a working electrode. The Hg / HgO electrode and the Pt sheet were used as a reference electrode and a counter electrode, respectively. The diaphragm was a Nafion proton exchange membrane. A 1M sodium hydroxide solution containing 50 mL of 20 mM HMF was used as an electrolyte. The reaction system was stopped after a charge of 579 C, and the product after electrocatalysis was detected by high performance liquid chromatography.

[0119] Fig.12 The graphs are the yield, Faraday efficiency and HMF conversion rate of the electrocatalytic oxidation of HMF to FDCA by CuCoNi electrode materials at different potentials. In the wide potential window of 1.43-1.63V vs.RHE, the yield, Faraday efficiency and HMF conversion rate of the electrocatalytic oxidation of HMF by CuCoNi electrode materials are all greater than 90%. At a potential of 1.53V vs.RHE, the yield, Faraday efficiency and HMF conversion rate of the electrocatalytic oxidation of HMF by CuCoNi electrode materials are all close to 100%. The excellent performance reflects the high efficiency of CuCoNi electrode materials in the electrocatalytic oxidation of HMF to produce FDCA.

[0120] The present invention provides a CuCoNi multi-transition metal-based oxide hydroxide surface mesh nano-spherical heterojunction bifunctional electrode material, which has a unique advantage of multiple active sites. The material is prepared by a basic copper salt loading method, calcination after electrodeposition, and a hydrothermal method; the synthesis method is simple and convenient, and the mild conditions are conducive to large-scale industrial production. The material can be applied to electrocatalytic reduction or electrocatalytic oxidation. The material has broad application prospects in the fields of electrocatalytic oxidation of biomass small molecules and electroreduction of nitrates, nitrites, organic nitrobenzenes and derivatives, has extremely high ammonia production and Faraday efficiency and extremely low nitrite accumulation in electrocatalytic reduction of nitrates to produce ammonia, and has excellent conversion rate, high selectivity, high Faraday efficiency and good stability in the electrocatalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid. It has broad market prospects in the fields of electrocatalytic organic synthesis and new energy.

[0121] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A CuCoNi multi-element transition metal-based bifunctional electrocatalyst, characterized in that: The bifunctional electrocatalyst is supported on a conductive substrate; the bifunctional electrocatalyst is an N-doped copper, cobalt and nickel-based oxide or hydroxide multiphase heterojunction material; The molar ratio of Cu to Co in the bifunctional electrocatalyst is 1:0.1-0.5, and the molar ratio of Cu to Ni is 1:0.8-1.5; The bifunctional electrocatalyst can be applied to electrocatalytic reduction or electrocatalytic oxidation.

2. The CuCoNi multinary transition metal-based bifunctional electrocatalyst according to claim 1, characterized in that: The bifunctional electrocatalyst presents a uniform nano-spherical structure, and the surface is densely covered with fine mesh-like porous structures.

3. The method for preparing the CuCoNi multinary transition metal-based bifunctional electrocatalyst according to claim 1 or 2, characterized in that: Includes steps: S1. Immersing the conductive substrate in a copper source solution to obtain a substrate loaded with basic copper salt after the reaction, washing and drying for later use; S2. constructing a three-electrode electrodeposition system with the basic copper salt-loaded substrate prepared in step S1 as the working electrode, wherein the electrolyte is a cobalt source solution, electrodepositing cobalt, washing and drying, and then calcining and annealing in an inert atmosphere; S3. The material obtained in step S2 is subjected to a hydrothermal reaction with a nickel source solution in an alkaline environment, and the CuCoNi multi-transition metal-based bifunctional electrocatalyst can be obtained after washing and drying.

4. The method for preparing the CuCoNi multinary transition metal-based bifunctional electrocatalyst according to claim 3, characterized in that: In step S1, the substrate material includes but is not limited to one or more of foamed nickel, foamed copper, and stainless steel mesh; And / or, in step S1, the copper source solution is any one of an aqueous solution of a copper salt, an ionic liquid solution of a copper salt, and a low-temperature molten salt of a copper salt; And / or, in step S1, the reaction temperature is 130-150° C. and the reaction time is 15-60 min.

5. The method for preparing the CuCoNi multinary transition metal-based bifunctional electrocatalyst according to claim 3, characterized in that: In step S2, during the electrodeposition process, the working electrode is a conductive substrate loaded with basic copper salt, the counter electrode is a graphite rod electrode, a platinum sheet or a platinum mesh electrode, the reference electrode is a calomel electrode, the electrodeposition potential is -1V vs. SCE, and the electrodeposition time is 500 to 1500s; In step S2, the calcination annealing process is carried out in a muffle furnace, the heating rate is 3-5°C / min, and the calcination time is 1-5h.

6. The method for preparing the CuCoNi multinary transition metal-based bifunctional electrocatalyst according to claim 3, characterized in that: In step S3, the hydrothermal reaction pH is 9-10, the hydrothermal temperature is 100-110° C., and the hydrothermal time is 8-12 h; The cobalt source includes but is not limited to at least one of nitrate, chloride, sulfate, phosphate, acetate and carbonate of cobalt; the nickel source includes but is not limited to at least one of nitrate, chloride, sulfate, phosphate, acetate and carbonate of nickel.

7. Use of the CuCoNi multinary transition metal-based bifunctional electrocatalyst according to claim 1 or 2 in electrochemical catalysis, characterized in that: Application in electrocatalytic reduction and / or electrocatalytic oxidation; When applied to electrocatalytic reduction, the bifunctional electrocatalyst serves as a cathode electrocatalyst; When applied to electrocatalytic oxidation, the bifunctional electrocatalyst serves as an anode electrocatalyst.

8. The use of the CuCoNi multinary transition metal-based bifunctional electrocatalyst according to claim 7 in electrochemical catalysis, characterized in that: The bifunctional electrocatalyst is used as a cathode electrocatalyst for the reduction of nitrates and nitrites to produce ammonia, the reduction of organic nitrobenzene and its derivatives to amines, and the electrocatalytic decomposition of water to produce hydrogen; The bifunctional electrocatalyst is used as an anode electrocatalyst and is applied to electrocatalytic oxidation of organic alcohols, organic aldehydes and biomass to produce high value-added chemicals.

9. The use of the CuCoNi multinary transition metal-based bifunctional electrocatalyst in electrochemical catalysis according to claim 6, characterized in that: The application system is a three-electrode system, using an H-type electrolytic cell, the three-electrode system includes a working electrode, a counter electrode, and a reference electrode; the bifunctional electrocatalyst is arranged at the working electrode; the pH of the electrolyte solution is in the range of 12 to 14, When applied to electrocatalytic reduction, the reduction electrolysis voltage is -0.5~0V vs.RHE. When applied to electrocatalytic oxidation, the oxidation electrolysis voltage is 1 to 2 V vs. RHE.

10. The use of the CuCoNi multinary transition metal-based bifunctional electrocatalyst in electrochemical catalysis according to claim 6, characterized in that: Applied to nitrate-containing wastewater treatment, soil management, and waste gas treatment; Or, applied in the field of synthesis of pharmaceutical intermediates; Or, applied in the field of synthesis of fine organic chemical intermediates; Or, applied in the field of new energy, used in water electrolysis to produce hydrogen, fuel cells, and zinc-air batteries.